The vertebrate habenula - Jesuthasan, Suresh (2020)
A renowned neuroscientist, now retired from Cambridge University, once told me that he had been a graduate student in North America when he first came across the term “habenula”. For him and his course mates, the habenula provided a source of humor. Nobody knew what it did, but the word sounded unusual and provoked a lot of laughter. The anatomy of habenula neurons, with their unusual terminations of loops and spirals at the midline, was a source of wonderment. There was nothing else like it in the vertebrate brain.